Curbing Misconduct in the Pharmaceutical Industry: Insights from Behavioral Ethics and the Behavioral Approach to Law. Issue 3 (1st October 2013) - Feldman, Yuval; Gauthier, Rebecca; Schuler, Troy
<x xml:space="preserve">Abstract</x> Two insights of psychology on which we would like to draw are that people react to law in more complex ways than rational‐choice models assume and that good people sometimes do bad things. With that starting point, this article provides a behavioral perspective on some of the factors that policymakers seeking to reduce the level of misconduct in the pharmaceutical industry should consider. Effective regulation and enforcement need to address the following questions: Who are the regulation's targeted actors — researchers or executives? Are the regulations directed toward research or marketing activities? Is the misconduct a product of explicit rational choice or implicit processes of which the actor is unaware? Is it reasonable to address all types of misconduct using the same approach? Certain misconduct — particularly by researchers — is due to automatic, intuitive, and unconscious decisions and needs to be addressed through different means than those used to address misconduct due to controlled, deliberate decisions. This article therefore recommends using different sorts of regulation depending on the context. It suggests more tailored enforcement mechanisms that will be sensitive to the pharmaceutical researchers' unique work motivations and to their awareness or lack of awareness of their own misconduct.